Correlations between primary tumour location, biomarkers of inflammation and lung injury, and postoperative pulmonary complications in patients underwent laparoscopic colorectomy: a propensity score matched analysis of 300 patients - Li, Hui-xian; Che, Li; Li, Yuan; Wang, Tai-hang; Min, Fang-di; Xu, Lei; Wang, Meng; Zheng, Zhao-xu; Qu, Shi-ning; Wang, Fei; Tang, Wei; Wei, Shi-jing; et al. (Frontiers in Immunology, 2025)
IntroductionThe impact of distinct primary colorectal cancer (CRC) sites on lung injury and complications remains largely unexplored, despite the palpable differences in surgical positions, procedures, and the resulting mechanically induced respiratory pressures at each site.Materials and methodsThis study employed a forwards-looking approach utilising the propensity score matching (PSM) method; 300 patients with pathological CRC after laparoscopic surgery from April 2019 to May 2023 were enrolled. Two categories were bifurcated based on their surgical locations: the rectosigmoid colon (RSC) group and the descending/ascending colon (DAC) group, with a 2:1 ratio. The occurrence of postoperative pulmonary complications (PPCs) within a 30-day postoperative period was meticulously evaluated. Additionally, assessments have been performed for plasma biomarkers of immune response dynamics and lung injury (plasma soluble advanced glycation end-product receptor [sRAGE], angiopoietin-2 [ANG-2], interleukin-1β/6 [IL-1β/IL-6]) and other parameters.ResultsAlthough the increase in postoperative lung epithelial damage, as indicated by the plasma sRAGE levels, was significant in the RSC group (DAC vs. RSC; 1029.6 [576.8–1365.2] vs. 1271.6 [896.3–1587.6]; odds ratio=0.999; 95% CI: 0.998 to 1.000; P=0.007), a significantly increased percentage of PPCs was observed in the DAC group (DAC vs. RSC; hazard ratio=1.669; 95% CI, 1.141 to 2.439; P=0.008). A univariate Cox proportional hazards model revealed that sRAGE, ANG-2, IL-1β, and IL-6 levels were not correlated with the incidence of time-to-PPCs across the two cohorts (P>0.05). Propensity score-weighted Cox regression and causal mediation analysis further demonstrated that the DAC site directly affected the incidence of PPCs, regardless of the other baseline confounders and clinical covariates related to the tumour site and PPCs.ConclusionThe primary site of CRC is an independent predictor of the development of PPCs. Despite the steep Trendelenburg position of the RSC group inciting more pulmonary stress, inflammation and lung epithelial injury, as indicated by higher sRAGE, it demonstrated a lower PPCs occurrence relative to its DAC counterpart, with a slightly inclined or reversed Trendelenburg position. None of the plasma biomarkers of inflammation or lung injury indicated sufficient prognostic value for PPCs.